ANALYSIS TYPES OF DEIXIS IN THE SPEECH TAYLOR SWIFT AT NEW YORK UNIVERSITY 2022 - Velin Jusbina Manalu; Lisbeth Juliana Sirait (Prodi Sastra Inggris UKI, 2024)
This research aims to analyze the types of deixis in Taylor Swift's speech at New York University in 2022. Using a descriptive qualitative approach, this research highlights the use of deixis in the context of public speeches and how deixis plays a role in interpreting contextual meaning in conversation. Through deictic analysis based on Levinson's theory of deixis, this research identifies personal, place, time, social and discursive deixis in the speech. Data was obtained from the transcript of Taylor Swift's speech and analyzed to understand the contextual meaning conveyed. The research results show that deixis plays an important role in conveying rich meaning in discourse. By using secondary data and simple random sampling techniques, this research succeeded in identifying 30 deixis in the speech. The implications of this research are to provide a deeper understanding of the use of deixis in the context of public speech and provide a basis for further research in the field of pragmatics.